The Use of Space on Living House as ‘Batik Tulis’ Business in Tourist Village of Batik Tulis Lasem - Arief Satya Wijaya; Titien Woro Murtini; R. Siti Rukayah (Tesa Arsitektur, 2019)
Batik workers in Babagan Village work in the room used in together with household activities. Working on batik does not require special space and can use any space. The utilization of space is analyzed by theory of the basic form of space, the nature of space, type of space and productive house. The method used in this research is qualitative method. There are 9 batik workers who become observation units to obtain information needed in the research. There is some space that is used for batik these are kitchen, yard, terrace, dining room, and living room, so batik can be done in public space, semi public and service room but not done in private space because pollution, lighting and natural air still less. Determination of space utilization based on its location close to kitchen, toilet, and tool or materials storage room, no pollution, no exposed to rain splashes, there is space that can use while taking care of children, has enough room. There is no batik space at batik workers' house, which is a place to make batik. Space has sufficient the extent of space required for the process of batik (nyanting). While the type of business space is a combination of mixed types and separate types.